Introduction To Mathematical Philosophy - Russell, Bertrand (Routledge, 1919)
This volume sets out in a lucid and non-technical way the main ideas of Principia Mathematica. It is as inspiring and useful to the beginner now as it was when it was first published in 1919.
Keywords: MATHEMATICS-PHILOSOPHY